2015
DOI: 10.1002/pssb.201552565
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical responses in hydrogenated graphene structures

Abstract: Abstractauthoren We present a theoretical study of the optical spin injection, optical current injection, and second harmonic generation of two 50% hydrogenated graphene structures: C16H8‐alt and C16H8‐up. Optical spin injection, under the incidence of circularly polarized light onto nonmagnetic semiconductors, creates spin‐polarized electrons in the conduction bands. Optical current injection and second‐harmonic generation are nonlinear second‐order effects that are allowed in materials without inversion symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…2, has hydrogen alternating on the upper and bottom sides of the carbon sheet. 37 Both the Up and the Alt structures are noncentrosymmetric, and therefore, they are good candidates in which SVI can be induced. In this article, we address theoretically the spin-velocity injection by one-photon absorption of linearly polarized light, analyzing in our structures two possible scenarios of practical interest.…”
mentioning
confidence: 99%
“…2, has hydrogen alternating on the upper and bottom sides of the carbon sheet. 37 Both the Up and the Alt structures are noncentrosymmetric, and therefore, they are good candidates in which SVI can be induced. In this article, we address theoretically the spin-velocity injection by one-photon absorption of linearly polarized light, analyzing in our structures two possible scenarios of practical interest.…”
mentioning
confidence: 99%
“…This effect has also been observed experimentally [6,7,8]. Interesting both nonlinear optical response and optical spin injection effects for partially hydrogenated semiconducting graphene have been predicted theoretically [9]. On the other hand, it has also been shown that hydrogenation of outer surfaces of graphene bilayers allows opening the tunable electron gap, which can be prospective in device application [3,10,11].…”
Section: Introductionmentioning
confidence: 79%
“…We demonstrate the energy dependent spin injections for 50% hydrogenated AA stacked graphene/h-BN bilayer in Fig. 7 (see also [9] for the formalism), leaving more detailed discussion of the linear and nonlinear optical response, its dependence on H dose and the structure specific optical signatures for the forthcoming paper [22]. Fig.…”
Section: Hydrogenated Bilayer and Trilayer Of Graphene/h-bnmentioning
confidence: 98%
See 1 more Smart Citation